The activity domain as the nexus of the organisation. (12th July 2011) - Taxen, Lars
The development, acquisition, adaptation, and diffusion of enterprise systems in organisations pose immense challenges. These challenges need to be addressed by considering the system in a wider context, where aspects of individual knowledge, sense-making, technology, and organising are taking into account. In this paper, the activity domain theory is suggested as a unifying framework for these areas in one respect – the coordination of actions. The central constructs in this theory are the activity domain, which frames a social unit providing some capability that the organisation needs; and the activity modalities, which represent innate predispositions for coordinating actions. Empirical results from the telecom industry are used to validate the approach in the areas of organisational design, information systems, and system engineering.